PEMBELAJARAN MENULIS TEKS DEBAT MENGGUNAKAN METODE PROBLEM BASED LEARNING BERBANTUAN MEDIA BONEKA KAUS KAKI PADA SISWA SMA KELAS X - Umi Mukhibatul Aslamiyah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The number of students who have difficulty in writing debate texts is the background for carrying out this research. The researcher uses the problem based learning method with the help of sock puppet media as a solution to overcome this problem. The purpose of this study is to know the scenario, implementation, teacher and student responses to learning to write debate texts in class X students using the problem based learning method assisted by sock puppet media and find out what difficulties are experienced by class X students in completing text writing tasks. debate. The research method used in this research is descriptive quantitative research method. Data collection techniques using observation instruments, lesson plans (Learning Implementation Plan), teacher and student response questionnaires and student ability tests. As a result, the implementation of teaching and learning activities carried out by the teacher was carried out according to the planned scenario. It can be seen from the results of the teacher activity observation sheet that gets a percentage of 47% and students as much as 60%. Then the responses of teachers and students get a percentage of agreeing 75% on the teacher's questionnaire and 49% on the student's questionnaire. The difficulties experienced by students when writing debate texts are found in the use of aspects of conclusions and effective sentences that are still not mastered by students.